PENGARUH LEADER-MEMBER EXCHANGE TERHADAP MOTIVASI INTRINSIK DENGAN PEMBERDAYAAN PSIKOLOGIS SEBAGAI PEMEDIASI PADA KSP CREDIT UNION DHARMA PRIMA KITA YOGYAKARTA - Ignatius Soni Kurniawan; Wiliam Kerby Pratama Bata Wahat (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of leader-member exchange on intrinsic motivation with psychological empowerment as a mediating variable. This research is a quantitative research using primary data. This research was conducted at the Credit Union Dharma Prima Kita Credit Union Savings and Loan Cooperative (KSP) office in Yogyakarta with a total of 50 respondents. Primary data was obtained from field surveys by distributing research questionnaires offline to employees. The analytical method used in this research is the classical assumption test and regression analysis. The results of the study found that the effect of leader-member exchange on intrinsic motivation was mediated by psychological empowerment.